2020
DOI: 10.1039/d0tc04627b
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable inkjet-printed electrochromic display for sustainable short-lifecycle electronics

Abstract: The fabrication of electronics on the basis of biofriendly materials aims to counterbalance the negative trends conveyed by the short life-cycle of electronics. Furthermore, these materials open the possibility to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 63 publications
0
51
1
Order By: Relevance
“…However, certified tests in a compost environment have revealed full biodegradability for a device made of the same cellulose acetate, a gelatin-based electrolyte, printed gold ink, and PEDOT:PSS. [97] Hence, the cellulose acetate likely constitutes the degradation bottleneck in water and such electronic devices require compost conditions to degrade properly.…”
Section: Fully Biodegradable Light-emitting Device Under Isotropic Be...mentioning
confidence: 99%
“…However, certified tests in a compost environment have revealed full biodegradability for a device made of the same cellulose acetate, a gelatin-based electrolyte, printed gold ink, and PEDOT:PSS. [97] Hence, the cellulose acetate likely constitutes the degradation bottleneck in water and such electronic devices require compost conditions to degrade properly.…”
Section: Fully Biodegradable Light-emitting Device Under Isotropic Be...mentioning
confidence: 99%
“…Another more recent example of a functional electrochromic device that incorporates water soluble PEDOT/PSS dispersions comes from the Hernandez-Sosa group who have reported on an inkjet printed biodegradable wearable electrochromic device. 25 The flexible and device architecture they developed involves PEDOT/PSS pixels connected to gold working electrodes and surrounded by a gold counter electrode, all of which is contained in a biocompatible gel electrolyte based on natural salts and gelatin-based hydrogel ( Fig. 5 ).…”
Section: Type I: Bleached To Coloured Materialsmentioning
confidence: 99%
“…Polymers, such as PET (polyethylene terephthalate) or PEN (polyethylene naphthalate) are typical substrates, but other substrates have also been evaluated, such as textiles by Wei et al [21]. Pietsch et al have demonstrated a bio-degradable EC display for sustainable short-life cycle electronics [22]. This display comprised of a poly (3,4-et hylenedi oxythiophene) : polystyr ene sulfonate (PEDOT:PSS) electrochromic layer, a gelatin-based electrolyte and gold electrodes deposited on a cellulose di-acetate substrate.…”
Section: Introductionmentioning
confidence: 99%